Spatial Navigation and Visuospatial Strategies in Typical and Atypical Aging - Laczó, Martina; Wiener, Jan M; Kalinova, Jana; Matuskova, Veronika; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (Brain sciences, 2021)
Age-related spatial navigation decline is more pronounced in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) dementia. We used a realistic-looking virtual navigation test suite to analyze different aspects of visuospatial processing in typical and atypical aging. A total of 219 older adults were recruited from the Czech Brain Aging Study cohort. Cognitively normal older adults (CN; n = 78), patients with amnestic MCI (n = 75), and those with mild AD dementia (n = 66) underwent three navigational tasks, cognitive assessment, and brain MRI. Route learning and wayfinding/perspective-taking tasks distinguished the groups as performance and learning declined and specific visuospatial strategies were less utilized with increasing cognitive impairment. Increased perspective shift and utilization of non-specific strategies were associated with worse task performance across the groups. Primacy and recency effects were observed across the groups in the route learning and the wayfinding/perspective-taking task, respectively. In addition, a primacy effect was present in the wayfinding/perspective-taking task in the CN older adults. More effective spatial navigation was associated with better memory and executive functions. The results demonstrate that a realistic and ecologically valid spatial navigation test suite can reveal different aspects of visuospatial processing in typical and atypical aging.
Keywords: mild cognitive impairment; spatial navigation; visuospatial functions; wayfinding; perspective taking; Alzheimer’s disease; navigation strategies; route learning